The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/asia.201900053
|View full text |Cite
|
Sign up to set email alerts
|

Glycopolymers Mimicking GM1 Gangliosides: Cooperativity of Galactose and Neuraminic Acid for Cholera Toxin Recognition

Abstract: Glycopolymers mimicking GM1 gangliosides were synthesized by incorporating multiple types of carbohydrates into the polymer backbone. The glycopolymers were immobilized onto gold surfaces, and the interactions with the cholera toxin B subunit (CTB) were analyzed using surface plasmon resonance imaging. The glycopolymer containing both galactose and neuraminic acid showed enhanced recognition of CTB. The interaction was enhanced mainly because of an improvement in the dissociation process by the binding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Underestimating the latter can totally offset the enthalpic benefit of cooperativity due to the entropic penalty associated with linker flexibility. 58,59 Recently, Zentel and coworkers 60 and Tacke and coworkers 61 conveyed compelling evidence of the potential of mimicking the selectin recognition properties of the sialyl Lewis x (SLe x ) tetrasaccharide (NeuNAc-a(2-3)-Gal-b(1-4)-[Fuc-a(1-3)]-GlcNAc) by the carbohydrate module approach for biomedical applications. Selectins are a family of cell adhesion molecules with an extracellular lectin domain that bind to fucosylated and sialylated glycoproteins and play a key role in the innate immune response.…”
Section: Carbohydrate-lectin Interactions In Heterogeneous Environmenmentioning
confidence: 99%
“…Underestimating the latter can totally offset the enthalpic benefit of cooperativity due to the entropic penalty associated with linker flexibility. 58,59 Recently, Zentel and coworkers 60 and Tacke and coworkers 61 conveyed compelling evidence of the potential of mimicking the selectin recognition properties of the sialyl Lewis x (SLe x ) tetrasaccharide (NeuNAc-a(2-3)-Gal-b(1-4)-[Fuc-a(1-3)]-GlcNAc) by the carbohydrate module approach for biomedical applications. Selectins are a family of cell adhesion molecules with an extracellular lectin domain that bind to fucosylated and sialylated glycoproteins and play a key role in the innate immune response.…”
Section: Carbohydrate-lectin Interactions In Heterogeneous Environmenmentioning
confidence: 99%
“…Previously, we reported that Fuc 100 and Gal 50 Fuc 50 block CTB binding to a fucosylated glycan, triLe x , but Gal 100 does not and that Gal 100 blocks CTB binding to GM1 but Gal 50 Fuc 50 does not . The incomplete blocking of GM1 binding to CTB by Gal 100 may have been because of the fact that the Gal of CTB-Gal 100 does not have multiple points of interaction like GM1 has with CTB . Blocking of CTB binding to the human primary intestinal epithelium can be accomplished with both galactosylated and fucosylated polymers …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the preparation of a biomimetic glycocalyxlike surface can provide a general strategy to obtain biomedical materials with good hydrophilicity, biocompatibility, and specific biomolecule recognition. 46,[106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121] In general, the preparation routes of a glycocalyx-like surface, i.e., glycosylation methods, can be divided into physical methods (e.g., physical adsorption and dipcoating), chemical methods (e.g., surface modification by glycopolymers, surface initiated polymerization of glycomonomers, and synthesis glycopolymers to prepare the substrates), and biochemical methods (e.g., enzymatic transglycosylation). 54,[122][123][124][125][126][127] For example, Bojarova et al reviewed the preparation routes and biomedical applications of glycomaterials (e.g., glyconanoparticles and glycodendrimers) based on the specific lectincarbohydrate interactions.…”
Section: Glycocalyxmentioning
confidence: 99%